Alar cartilage hematoma of the nose secondary to facial trauma. - Magboul, Nasir A.; Al-Amri, Deafullah (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
A 27 years old male patient victim of road traffic accident presented to emergency department by ambulance team with ankle swelling and decrease range of motion, seen by orthopedic team and admitted as case of right ankle fracture for surgical intervention. Patient then referred to otolaryngology regarding on and off nasal bleeding and right nasal swelling arising from inner surface of right lower lateral cartilage of the nose 6 hour after the facial trauma, we present this case of hematoma of lower lateral cartilage which consider as one of the unique and rare condition following nasal and facial trauma. Early recognition of this condition is important, also differentiation between alar hematoma and septal cartilage hematoma is not easy for non-otolaryngology doctor, so increase awareness of this condition as one of possible sequel of fecal trauma and early referral to otolaryngology services is crucial. We present here a case of right sided alar cartilage hematoma, including the approach, management and follow up of the patient. We recommend early surgical drainage to optimize aesthetic out come after trauma.